Igrzyska olimpijskie w Berlinie w roku 1936 w oczach przebywających w Niemczech Amerykanów - Sołuba, Paulina (Acta Universitatis Lodziensis. Folia Historica, 2014)
On 13th May 1931 the Weimar Republic was appointed by the International Olympic Committee (IOC) to host the Olympic Games 1936. Adolf Hitler, who was elected Chancellor of Germany January 30, 1933 finally responded positively to the idea of the Olympics. Due to the anti-Jewish policies of Berlin in Semitic environments appeared, especially in the U.S., the idea of a boycott of the Olympics in 1936 or move the event to another state. Do not, however, decided to take this step. The Olympic Games were run from 1 until 16 August 1936. For this reason, Americans who want to watch the games in July began arriving by sea to Germany. Among them were correspondents, sports journalists, diplomats, businessmen and tourists. American sports team also came to Germany. During sporting competitions U.S. citizens closely observed the reality of the Third Reich. Nazi propaganda had a big impact on the views of Americans about the new Germany.